Herpes zoster infection of the face: A case report with review of literature - Seetharamiah Sunder Raj (Journal of Indian Academy of Oral Medicine and Radiology, 2017)
Varicella zoster virus (VZV) is a DNA virus and a member of the alpha herpes viridae family, causing both primary and recurrent infection. Herpes zoster (HZ), commonly called shingles, is a distinctive syndrome caused by reactivation of VZV. This reactivation occurs when immunity to VZV declines because of aging or immune-suppression. HZ can occur at any age but most commonly affects the elderly population. HZ may affect any sensory ganglia and its cutaneous nerve. Most of the infections affect dermatomes of T3 to L2, but approximately 13% of the patients present with infections involving any of the three branches of the trigeminal nerve. Prodromal symptoms include neuropathic pain, headache, malaise, and disrupted sleep. HZ causes pruritic, localized, vesicular rash which usually appears unilaterally in the distribution of one or more adjacent sensory nerves accompanied by neuropathic pain in the affected dermatome. This is a case report of HZ infection in a 55-year-old male patient who was managed with comprehensive medical treatment.